Car Information Bus Image Restoration Using Multi-wavelet Transform Algorithm - Zhuang Wen Wu; Liangrong Zhu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Car reverse image is transmitted by information bus. Because of the bad electromagnetic environment of the engine compartment, car’s information bus sometime will be blocked or not real-time, which can lead to the uncertainty of information transmission, and will cause the risks of security and reliability of the transmitted network. A GHM multi-wavelet is adopted by this paper to restore the interference car reverse image. After balanced processing the GHM multi-wavelet, constant module blind equalization algorithm based on balanced orthogonal multi-wavelet transform (MWTCMA) is used in this paper. Compared with the constant module blind equalization algorithm (CMA) and wavelet transform constant module blind equalization algorithm (WTCMA), results show that MWTCMA can eliminate the multi-wavelet pre-filtering process through multi-wavelet transform on input signal, and improve the convergence speed. The calculation error of MWTCMA is also smaller than the other two methods.DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.2697